Efforts to Improve Al-Kulliyatu Al-Khamsah's Attitude in the Daily Life of Class X Students of SMK N1 Kepenuhan Hulu - Leni, Mesis; Kasmawati, Kasmawati; Fitri, Umi (Indonesian Journal of Basic Education, 2024)
This research aims to improve the understanding and application of al-Kulliyatu al-Khamsah values in the daily life of SMK N1 Kepenuhan Hulu grade X students. Al-Kulliyatu al-Khamsah is the five main principles in Islam, namely safeguarding religion (hifzhud-din), protecting the soul (hifzhun-nafs), safeguarding intellect (hifzhul-aql), safeguarding offspring (hifzhun-nasl), and safeguarding treasure (hifzhul-mal). The research method used is classroom action research with the Kemmis and McTaggart model, which includes planning, action, observation, and reflection. Data was collected through observation, interviews, and questionnaires. The results of the study show that through learning based on Islamic values and hands-on practical activities, there is a significant increase in students' understanding and attitude towards al-Kulliyatu al-Khamsah. This study concludes that learning strategies based on religious values can effectively increase students' positive attitudes in daily life.